2012
DOI: 10.2501/ijmr-54-1-129-145
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting Self-Reported Attitudinal Data for Mischievous Respondents

Abstract: For various reasons, survey participants may submit phony self-reports meant to avoid researcher skepticism. Although casewise deletion of subtly suspicious attitude data is not standard practice, marketing research might improve if these bogus cases were purged before substantive data analyses. After suggesting reasons for a new category of p r o b l e m a t i c s u r v e y p a r t i c i p a n t -t h e mischievous respondent-and reviewing the related response bias, faking, inattentive respondent, and outlier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 74 publications
(155 reference statements)
0
23
0
Order By: Relevance
“…Prior research has revealed that a quite substantial proportion of participants in CEs make random choices (many of which are probably “mischievous respondents,” cf. Hyman & Sierra, 2012); this can lead to severely attenuated parameter estimates if not controlled (Grunert et al, 2015). The LGC module enables identifying participants whose choices are not related to the alternatives' attributes at all.…”
Section: Resultsmentioning
confidence: 99%
“…Prior research has revealed that a quite substantial proportion of participants in CEs make random choices (many of which are probably “mischievous respondents,” cf. Hyman & Sierra, 2012); this can lead to severely attenuated parameter estimates if not controlled (Grunert et al, 2015). The LGC module enables identifying participants whose choices are not related to the alternatives' attributes at all.…”
Section: Resultsmentioning
confidence: 99%
“…For Harman's singlefactor test, results of the unrotated EFA solution for PCA and MLE show a multifactor solution and first-factor explained variance of 25.07%; CFA results also are robust.These results, along with low intra-respondent variance (Hyman and Sierra, 2012), suggest CMB did not meaningfully affect the studied relationships.…”
Section: Common Methods Biasmentioning
confidence: 62%
“…Again, the CFA-based multi-trait multi-method technique and Harman's single-factor test, along with low intra-respondent variance (Hyman and Sierra, 2012), indicate no CMB concerns; the CFA results reveal valid and reliable measures and the unrotated EFA solution (for both PCA and MLE) reveals a multi-factor solution with first-factor explained variance of 28.27%.…”
Section: Common Methods Biasmentioning
confidence: 99%
“…We suspected that the high-PTE respondents were not outliers in the traditional sense, in that their responses were not simply extreme versions of true scores, but rather that because of the large, online commercial panel data-context of data collection, many of these respondents were not sufficiently attending to survey items or were simply falsifying data to get through the reporting task with minimal effort. Such concerns have been noted in the literature concerning mischievous respondents (Hyman & Sierra, 2012;Robinson-Cimpian, 2014) and so-called professional respondents in large online data collection (Hillygus et al, 2014). After several rounds of data analytics (Verkuilen & Rasmussen, 2020), we decided to identify these aberrant respondents using a two-tiered identification strategy: One tier examined patterns of reporting across types of PTEs using latent profile analysis (LPA), and another tier limited the number of statistically extreme counts of PTEs per respondent.…”
Section: Participants and Proceduresmentioning
confidence: 99%